Multifactorial Ergonomic Assessment Identifies Posture as the Dominant MSD Determinant: Penilaian Ergonomi Multifaktorial Mengidentifikasi Postur Tubuh sebagai Faktor Penentu Utama Gangguan Muskuloskeletal (MSD) - Raditya Ayuningtyas; Zufra Inayah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Musculoskeletal disorders (MSDs) are among the most prevalent work-related health problems affecting workers in the informal sector worldwide. Specific Background: Tailors are particularly vulnerable to MSDs because prolonged static postures, repetitive movements, and extended working hours substantially increase musculoskeletal strain. Research Gap: However, evidence identifying the dominant determinants of MSDs complaints among informal-sector tailors, particularly in developing-country settings, remains limited. Objective: This study aimed to identify the dominant factors associated with MSDs complaints among informal-sector tailors in Gresik Regency, Indonesia. Methods: A quantitative cross-sectionall study was conducted involving 78 tailors using a total sampling approach. MSDs complaints were assessed using the Nordic Body Map (NBM), working posture was evaluated using the Rapid Upper Limb Assessment (RULA), while temperature and lighting conditions were measured using a thermometer and a lux meter. Data were analyzed using Chi-square tests followed by multiple logistic regression. Results: Sex (p = 0.022), working duration (p = 0.001), and working posture (p < 0.001) were significantly associated with MSDs complaints. Multivariable analysis demonstrated that prolonged working duration (OR = 6.491; 95% CI: 1.658–25.410) and poor working posture (OR = 16.941; 95% CI: 4.476–64.123) were significant predictors, with working posture emerging as the strongest determinant of MSDs complaints. Novelty: This study provides evidence on the relative contribution of individual, occupational, and environmental factors in explaining MSDs complaints, highlighting working posture as the primary determinant among informal-sector tailors. Implications: These findings support the implementation of ergonomic interventions and working-hour management strategies to reduce the risk of MSDs among informal-sector tailors. Highlight: Working posture identified as the dominant MSD risk factor. Working more than 8 hours increased MSD complaints. Ergonomic improvements are recommended for informal-sector tailors. Keywords: Musculoskeletal Disorders, Tailor, Informal Workers, Working Posture, Ergonomics